1993
DOI: 10.1007/bf00300077
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis biofilms and the encrustation of urethral catheters

Abstract: Bacterial biofilms were observed on 69 of 75 catheters taken from patients undergoing long-term bladder management. Ten catheters were colonized by pure cultures of Proteus mirabilis. In each of these cases the bacteria formed layers on the catheter surface, underlying encrustations of struvite and hydroxyapatite which partially or completely occluded the catheter lumen. Encrustation was also apparent on catheters colonized by P. mirabilis plus other species, but was rarely seen on catheters colonized by non-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 20 publications
4
88
0
4
Order By: Relevance
“…Significantly, species capable of producing the enzyme urease are predominant. 10 Urease is the catalyst that generates the crystals, hydrolyzing urea in the residual bladder urine to produce two molecules of ammonia to every molecule of carbon dioxide causing a rise in pH. As the urine becomes alkaline, crystallization of the magnesium and calcium phosphates is induced.…”
Section: Nature Of Encrustationmentioning
confidence: 99%
“…Significantly, species capable of producing the enzyme urease are predominant. 10 Urease is the catalyst that generates the crystals, hydrolyzing urea in the residual bladder urine to produce two molecules of ammonia to every molecule of carbon dioxide causing a rise in pH. As the urine becomes alkaline, crystallization of the magnesium and calcium phosphates is induced.…”
Section: Nature Of Encrustationmentioning
confidence: 99%
“…8 Furthermore, the relationship between Proteus bacteriuria and urinary catheter encrustation and blockage is well documented. 9,10 Proteus bacteriuria has likewise been documented in persons with SCI, 1,11,12 but not specifically in association with stones. Two retrospective reports published two decades ago of almost 6000 patients with SCI found that bladder calculi were associated with the complete injuries and with Klebsiella bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…O biofilme é um material que consiste de bactéria com polissacarídeo extracelular (slime) e contém íons de cálcio e magnésio, a proteína Tamm-Horsfall da urina e ocasionalmente estruvita de organismos produtores de urease (Nicolle, 2001). O biofilme contribui para o bloqueio do cateter, o qual está relacionado com a infecção urinária causada por Proteus mirabilis (Kunin, 1989;Mobley e Warren, 1987;Stickler et al, 1993;Struble et al, 2009).…”
Section: Methodsunclassified
“…Ainda não existem métodos disponíveis para o controle efetivo do problema (Jones et al, 2005b). Devido à importância da incrustação no desempenho dos cateteres urinários, este assunto vem sendo estudado por Barford et al (2008), Bettio et al (2008a, b), Camargo et al (2005a, b), Jones et al (2005a, b), Lawrence e Turner (2005), Mathur et al (2006), Pizzolitto et al (2002), Santos e Pizzolitto (2007, 2008, Santos et al (2008a, b, c), Shaw et al (2005), , Stickler et al (1993), Stickler e Morgan (2008) e Tunney et al (1997). O objetivo do presente estudo foi investigar a formação de biofilme cristalino no lúmen interno de cateter urológico.…”
Section: Methodsunclassified